PRACTICAL ASPECTS INVOLVED IN TECHNOLOGICAL ALGORITHM FOR MAKING FIXED PROTHESES USING DIGITAL METHODS - Irina Grădinaru; Alice Arina Ciocan Pendefunda; Loredana Liliana Hurjui; Balcoș Carina; Mihaela Mitrea; Oana Adina Armencia; Magda Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2021)
Ceramic restorations on zirconia framework can be used in different areas of the dental arch, integrating perfectly and can be indicated, concomitantly, in some coronal conditions such as dyschromia, moderate dental abrasions, dystrophies, incipient carious processes, dental dwarfism, dysplasia, dental fractures in the incisal third of the dental units and other malpositions, providing patients with superior results through good marginal adaptation and restoration of interdental relationships. CAD/CAM systems are now widely used in dentistry to make dental restorations. The introduction of these systems in dentistry has made it possible to meet the expectations of patients, who, with the help of chair-side systems, can benefit from high quality and precise prosthetic restorations in a single treatment session. The aim of this study is to individualize the correlation between the clinical and technological stages, the therapeutic solutions being anchored in the non-metallic register, the treatment decision being made according to the particularity of the clinical case, in order to achieve the final clinical success through the aesthetic requirements.